The Role of Guidance and Counseling in Strengthening Students' Career Preparation - Refid Samudra; Muhammad Nur Wangid (STAI Hubbulwathan Duri, 2024)
The concern between choosing to work or pursuing higher education is a common dilemma that many students face. Counselling Teachers can provide support through individual counseling services, helping students understand their potential and desires. This research uses a systematic literature review method. The article search began by visiting Google scholar by entering the keywords counseling and career students. Based on the search using these two keywords, 78 articles were obtained. A systematic search of articles was conducted on Google Scholar using the keywords 'counseling' and 'career student', which yielded 78 articles. After applying certain inclusion criteria, 25 relevant articles were selected for review. Based on the research findings, it can be concluded that guidance and counseling teachers have the main responsibility in helping students understand the career world, recognize talents, and provide information about career choices. Through individual guidance services, skill development, and social support, Guidance and Counseling teachers play an important role in preventing and overcoming students' career problems. Based on the conclusions obtained, it is necessary to develop special programs for counseling services to support students' career stability tailored to school conditions and environmental conditions. The hope is that students can develop their potential both to work and continue to a higher education level. Schools can work with counselors and educators to develop comprehensive career development programs that integrate career exploration activities, skill-building workshops and real-world experiences into the curriculum. For example, schools can organize career fairs, internship opportunities and mentorship programs to introduce students to various career paths and industries.